Phosphorus and calcium intake of stunted toddlers aged 24-59 months: A case-control study in Sinar Bahagia Village, Simeulue - Alda Wati; Suryana Suryana (JAND: Journal of Applied Nutrition and Dietetic, 2021)
Stunting is still a serious problem in toddlers and is usually caused by insufficient calcium and phosphorus intake, which plays an important role in bone formation. This study aimed to analyze the phosphorus and calcium intake of stunted toddlers aged 24-59 months in Sinar Bahagia Village, Simeulue Barat District, Simeulue Regency. This research was a case-control study. The sample of this study was stunted and non-stunted children. Each case and control group consisted of 62 subjects who were selected using the simple random sampling technique. Food recall and food frequency questionnaire (FFQ) were used to investigate nutrient intake. NutriSurvey was used to analyze the content of nutrient intake. Meanwhile, the chi-square test was used to analyze the effects of calcium and phosphorus intake on the incidence of stunting. Stunted children had lower calcium and phosphorus intakes than non-stunted children (P-value <0.05). Stunted children had 2.879 times lower phosphorus than the control group. Moreover, they had 35 times lower calcium intake than the control group. Serious stunting problems in children require a nutritional counseling program that trains mothers to meet children’s daily food intake, especially high calcium and phosphorus.